(untitled) (Journal of Engineering, 2014)
Low-level microbial activity due to the production of organic acids is a recognized problem during the initial phase of food waste composting. Increasing such activity levels by adjusting the pH values during the initial composting phase is the primary objective to be investigated. In this study, sodium acetate (NaoAc) was introduced as an amendment to an in-vessel composting system. NaoAc was added when the pH of the compost mixture reached a low level (pH < 5), the addition increased pH to 5.8. This had a positive effect on the degradation of organic materials i.e. the formation of methane gas compared to the results without NaoAc addition. The results also proved that anaerobic-aerobic in-vessel composting could reduce the large amounts of wastes by 33% -30%. However the addition of NaoAc had no significant influence on temperature profile, bulk density, electric conductivity (EC), moisture contents, Nitrogen, phosphorus, potassium (NPK) and heavy metals )Cu, Cd, Ni, Pb) during the composting process, in fact heavy metals and (NPK) were below the maximum permissible levels of the Japanese organic farming and the USDA and US Compost Council standards . To assess the performance of the composting process, two small-scale digesters were used with fixed temperature. Maximum methane content of 68±1% and 75±1% by volume of the generated biogas was achieved in the run without and with NaoAc respectively. The germination index was which proved that the stabilized compost obtained in this research is of the “mature" kind and it is satisfactory for agricultural use according to the organic farming recommended by the Japanese Ministry of Agriculture, Forestry and Fisheries, and USDA and US Compost Council standards.